Inbound supply chain management in the automotive industry of South Africa during a recession. - Müller, Herman (My University, 2012)
Automotive manufacturers inbound supply chains span across borders and across continents. Due to this, economic events such as recessions have a direct impact on these inbound supply chains. Automotive manufacturers within South Africa source components on a global scale. Multiple suppliers supply Tier 1 suppliers of components and parts that, in turn, are supplied to the automotive manufacturers‟ plants. This study reviews the impact that recessions have on the inbound supply chain of automotive manufacturers within South Africa, and specifically evaluates the impact on the Tier 1 suppliers within the automotive manufacturing process. The impact of the December 2007 recession was investigated by semi structured interviewing of ten Tier 1 suppliers within South Africa. This process identified areas within their companies where the recession had a direct impact. The study found that Tier 1 suppliers experienced the recession on key areas such as downsizing of staff, high inventory levels (Bullwhip effect), cash flow, exchange rate exposure, capital investment, demand / forecasting accuracy and supplier bankruptcy. The severity of the impact of the recession was however, the occurrence of all the above at the same time. This created a “perfect storm” scenario for the Tier 1 suppliers to overcome. The study‟s objective is to highlight the impact of recessions on automotive manufacturers inbound supply chains as well as to assist these organisations in understanding the impact that all of these risks occurring simultaneously will have on them. The study also serves to emphasise the importance of designing scenarios and strategies that will continue to manage organisations through recessions. By creating impact awareness, supply chain executives and engineers will be able to create the necessary strategies to minimise the impact that recessions could have on their organisations.
MBA thesis - WBS
Keywords: Supply chain management; Automotive industry